ショウワ キチ ノ シンジシンケイシツ ト ジシン ケンチリツ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 神沼, 克伊; カミヌマ, カツタダ; 千葉, 平八郎; チバ, ヘイハチロウ; KAMINUMA, Katsutada; CHIBA, Heihachiro (国立極地研究所, 1973)
P(論文) A new vault for seismographs was built at Japanese Antarctic Station Syowa (SYO) and the observation of the HES and the Long-Period seismographs started on March 1, 1970. The old seismograph room was not adequate for detecting the extreme micro-seismic activities when the wind velocity exceeded 10m/s. In the new vault, however, the earthquakes can be identified even when the wind velocity is over 20m/s in summer and 30m/s in winter. The earthquake detection capability in the new vault is reported here. We examined how many earthquakes reported in the summary report of NOAA were detected as P phase groups (P and PKP) on the HES seismograms at SYO during the period from March to December, 1970. The detection capability of SYO is 23%, which is a few times larger than that of the old one. The detection capability is discussed in connection with the magnitude and the epicentral distance, and is compared with those at other stations. departmental bulletin paper